Solitary plasmacytoma of the tibia: literature review and case report - Hu, Xianwen; Li, Dandan; Hu, Xiao; Li, Shun; Wang, Pan (Frontiers in Oncology, 2026)
Solitary plasmacytoma (SP) is seldom encountered. It can affect any bone in the body, but is more common in the spine, especially in the thoracic region, while SP in the tibia is relatively rare. Herein, we report the case of a 34-year-old woman who visited our hospital with right calf pain for over a month. The X-ray, computed tomography (CT), and magnetic resonance imaging (MRI) revealed a tumor growing along the longitudinal axis of her right tibia, which was suspected to be malignant. The patient subsequently underwent a puncture biopsy, and the pathological results revealed a plasma cell myeloma. To further evaluate the extent of tumor involvement, the patient underwent single-phase technetium-99 labeled methylene diphosphonate (99mTc-MDP) single photon emission computed tomography (SPECT) whole-body bone imaging, and the results showed no significant radioactive concentration in the entire body except for the right proximal tibia. Based on these imaging features and pathological results, the patient was diagnosed with SP. We summarized the clinical features and imaging findings of tibial SP based on our case and the published literature The results showed that SP is more likely to occur in young people. Its imaging has a certain specificity, which is characterized by a uniform low - density shadow growing along the longitudinal axis, without a sclerotic rim, and increased radioactive uptake on whole - body bone imaging. MRI showed long signals on T1 and T2, with significant enhancement on contrast-enhanced scans, but rarely breaking through the bone cortex to form soft tissue masses. The current study suggests that a thorough understanding of the clinical and imaging characteristics of the tibial SP can increase the likelihood of obtaining an accurate diagnosis before surgery.